Identification of DNA-Methylated CpG Islands Associated With Gene Silencing in the Adult Body Tissues of the Ogye Chicken Using RNA-Seq and Reduced Representation Bisulfite Sequencing - Lim, Won-Jun; Kim, Kyoung Hyoun; Kim, Jae-Yoon; Jeong, Seongmun; Kim, Namshin (Frontiers in Genetics, 2019)
DNA methylation is an epigenetic mark that plays an essential role to regulate gene expression. However, little is known about gene expression levels associated with DNA methylation in an adult tissue at the genome-wide level. Expression levels are rarely affected by DNA methylation in normal adult tissues; however, we focused on small differences in expression level that occur as a result of DNA methylation. In this study, we examined 20 pairs of methylomes and transcriptomes from normal adult tissues using two different next-generation sequencing techniques, RNA-seq and RRBS. A total of 3,133 CpG islands were identified from 20 pairs of intra individual data which could affect downstream genes. Analyzing these CpG island and gene pairs, 120 significant units were statistically correlated. Among them, 6 genes (CLDN3, DECR2, EVA1B, NME4, NTSR1, and XPNPEP2) were highly significant, and their expression was regulated by alteration of DNA methylation. Additionally, 3 genes (FOXG1, MEIS1, and PRDM16) are associated with genomic imprinting as well as tissue development. Finally, our data demonstrated how DNA methylation correlated to gene expression in normal adult tissues.